Pengaruh Lingkungan Budaya Terhadap Kegiatan Bisnis Mcdonald’s Dalam Skala Internasional - Suprapto, Yandi; Cornelyanto, Edward; Febriyanti, Febriyanti; Yeo, Jacelyn Christina; Rina, Rina (Program Pascasarjana STIE Amkop Makassar, 2023)
With the development of technology and information fields, it has allowed foreign companies or businesses from one country to enter into another country. This must have been a very good opportunity for all companies around the world. However, there is an important thing or point in determining the success or failure of a company in implementing an international scale business, namely understanding the cultural environment or culture of various regions. In general, culture can have an impact on some activities or business aspects, such as communication; negotiation & decision making; the value of beliefs; business practices; consumer preferences or interests up to human resource management. One of the companies engaged in an international scale is McDonald's, where McDonald's is a fast food business that is very active in doing business on an international scale. The research method used is a qualitative method. Qualitative research does not use statistical data but rather through data collection which is then analyzed and interpreted. Keywords: Cultural Environment; International; McDonald’s